Legal Construction of Home Ownership Financing According to Sharia Principles - Maripah, Emma; Zainusyukur, Zainusyukur (Ridwan Institute, 2025)
Sharia Home Ownership Financing (PPR Syariah) is an urgent need for the Indonesian Muslim community in obtaining housing according to Islamic principles. This study aims to analyze the juridical construction of PPR Syariah that is ideal for Indonesia through a normative juridical approach with descriptive-prescriptive analysis. Secondary data were collected through a literature study and reinforced primary data from stakeholder interviews. The findings show that Sharia PPR in Indonesia faces complex problems: Islamic bank mortgages are still under criticism related to sharia compliance, while non-bank sharia PPRs are weak in regulation even though they are considered more sharia by the community. The realization of Sharia mortgages has only reached 15.9% of total housing financing, far from the potential of the Muslim market of Rp. 720 trillion. The housing backlog of 12.75 million units requires financing solutions that accommodate the religiosity of the community. The ideal juridical construction requires a holistic system approach based on Maqasid Syariah by considering aspects of sharia (sharia conformity) and qonunan (positive law). The construction model must involve community participation (legal culture) in the formation of policies (legal policy) towards a comprehensive Sharia PPR Law. The study recommends the establishment of special regulations that accommodate both Islamic bank mortgages and non-bank Islamic PPRs with adequate supervision.